(untitled) (The Journal of Psychology and Sociology, 2017)
This article dedicated to psychological research of motivation of professional sportsmen in big tennis of Kazakhstan. The practical significance of the work connect with the fact that the results of this work can be used by coaches tennis academies, private coaches, sports psychologists. In the study involved 48 professional tennis players who were divided into 2 groups according to gender. All participants are professional sportsmen representing sports interests not only in Kazakhstan, but also abroad. There were conducted techniques such as test questionnaire to measure achievement motivation (TMD) A. Mehrabian, method of determining the orientation to success and avoiding failure A.A. Rean, method of diagnosis of personality motivation to succeed T. Ehlers and evaluation of an athlete conditions effective workout B.J. Kretti. Statistical analysis performed with psychological methods using the criterion of Mann-Whitney U-test and Spearman correlation coefficient SPSS15 in order to identify significant differences in psychological characteristics of motivation among professional tennis players between the groups by gender. The study revealed that the motivation to achieve success in sport is a psychological feature of all the participants.